Financial Losses Arising from Cattle Organ and Carcass Condemnation at Lokoloko Abattoir in Wau, South Sudan. (20th March 2023) - Taha, Alfateh; Saad, Shereen; Jubara, Ambros; Wani, Charles; Phiri, A. M.; Simuunza, Martin; Munyeme, Musso; Hang'ombe, Bernard; Mumba, Chisoni
Abstract : Slaughterhouses in South Sudan mirror the economic losses resulting from cattle organs and carcass condemnation due to zoonotic and epizootic diseases of livestock, such as tuberculosis, cysticercosis, and hydatidosis in cattle. However, due to the war, slaughterhouse record keeping has been inconsistent in South Sudan, and thus the estimation of diseases in cattle and their impact may be underestimated. Therefore, this study was conducted to estimate the major causes of carcasses and organ condemnation of cattle slaughtered at Lokoloko abattoir and the resulting financial losses. A cross-sectional active abattoir survey involving antemortem and postmortem examinations was conducted on 310 cattle between January 2021 and March 2021. Furthermore, five-year (September 2015–September 2020) retrospective data on meat inspection records were also collected and analyzed. During the antemortem inspection of the active abattoir survey, 103 (33.2%) cattle had signs of disease. These signs included herniam 17 (5.5%), local swelling 16 (5.2%), lameness 15 (4.8%), emaciation 13 (4.2%), blindness 12 (3.9%), depression 11 (3.5%), pale mucus membrane 7 (2.3%), nasal discharge 5 (1.6%), lacrimation 4 (1.3%), and salivation 03 (0.97%). Postmortem inspection revealed gross pathological findings on 180 (58.6%) carcasses, out of which 47 (26.1%) livers and 31 (17.2%) hearts were condemned due to various causes. The active abattoir survey and the retrospective data revealed that tuberculosis, fascioliasis, hydatidosis, and heart cysticercosis were the leading causes of condemnation of carcasses and organs. In the active abattoir survey, a total of 19, 592, 508 South Sudanese Pounds, equivalent to US$29, 686 was lost from organ condemnation, while in the retrospective data; the overall direct financial loss during the five years was estimated to be 299, 225, 807 South Sudanese Pounds equivalent to US$453, 372. This study revealed that bacterial and parasitic diseases were the common causes of carcass and organ condemnations and caused significant financial losses at Lokoloko abattoir in Wau, South Sudan. Therefore, there is a need for training farmers on cattle disease management, heightened meat inspections, and proper disposal of condemned meat.